Environmental release of core–shell semiconductor nanocrystals from free-standing polymer nanocomposite films. Issue 3 (12th May 2016) - V. Pillai, Karthik; Gray, Patrick J.; Tien, Chun-Chieh; Bleher, Reiner; Sung, Li-Piin; V. Duncan, Timothy
Abstract : This work presents a new approach to study mechanisms and particle-size dependence of environmental release of nanoparticles from polymer nanocompsites using fluorescent quantum dots. Abstract : Concomitant with the development of polymer nanocomposite (PNC) technologies across numerous industries is an expanding awareness of the uncertainty with which engineered nanoparticles embedded within these materials may be released into the external environment, particularly liquid media. Recently there has been an interest in evaluating potential exposure to nanoscale fillers from PNCs, but existing studies often rely upon uncharacterized, poor quality, or proprietary materials, creating a barrier to making general mechanistic conclusions about release phenomena. In this study we employed semiconductor nanoparticles (quantum dots, QDs) as model nanofillers to quantify potential release into liquid media under specific environmental conditions. QDs of two sizes were incorporated into low-density polyethylene by melt compounding and the mixtures were extruded as free-standing fluorescent films. These films were subjected to tests under conditions intended to accelerate potential release of embedded particles or dissolved residuals into liquid environments. Using inductively-coupled plasma mass spectrometry and laser scanning confocal microscopy, it was found that the acidity of the external medium, exposure time, and small differences in particle size (on the order of a few nm) all play pivotal roles in release kinetics. Particle dissolution was found to play a major if not dominant role in the release process. This paper also presents the first evidence that internally embedded nanoparticles contribute to the mass transfer, an observation made possible via the use of a model system that was deliberately designed to probe the complex relationships between nanoparticle-enabled plastics and the environment.